Pemberdayaan Ibu-Ibu Rumah Tangga melalui Workshop Batik Ecoprint: Implementasi Nilai-Nilai Pancasila pada Masyarakat Dusun Salam Kelurahan Randuacir Kota Salatiga - Agusman, Ferdinan; Dwi Rahmawati, Ninda Yulia; Handayani, Artri Damai; Setyowati, Erna (Universitas Negeri Semarang, 2025)
The Batik Ecoprint Workshop in Dusun Salam, Salatiga, is an initiative aimed at empowering housewives by combining cultural preservation, eco-friendly innovation, and the application of Pancasila values. The activity was attended by 11 participants representing the RW 01 PKK, who were trained in batik- making using fresh leaves and flowers with natural dyeing techniques. The implementation method included seven stages, from introduction to evaluation. The results showed that the participants successfully mastered the batik ecoprint technique and applied Pancasila values such as mutual cooperation and environmental stewardship. This workshop is expected not only to provide technical skills but also to internalize Pancasila values, open up additional economic opportunities, support cultural sustainability and eco-friendly practices, and potentially enhance the economic and social well-being of the community.